Online naphazoline quality control by micellar-enhanced spectrofluorimetry - Peralta, Cecilia Mariana (2011)
The aim of this study was to develop a method for online spectrofluorimetric quality control of naphazoline (NPZ) in pharmaceuticals and raw drugs. A combination of a flow-injection analysis (FIA) system with micellar-enhanced fluorescence detection is presented as a powerful alternative for the rapid and sensitive analysis of naphazoline. Since NPZ shows low native fluorescence, the use of an anionic surfactant, such as sodium dodecyl sulphate (SDS), provides a considerable enhancement of fluorescence intensity and the nature of the technique allows a possible and easy adaptation to a FIA system. Using λ exc = 280 nm and λ em = 326 nm, a good linear relationship (LOL) was obtained in the range 0.003-10 μg mL -1 with a detection limit (LOD) of 3 × 10 -4 μg mL -1 (s/n = 3). Parameters related to the nature of the analytical signal and to the FIA manifold were optimized. Satisfactory recoveries were obtained in the analysis of commercial pharmaceutical formulations. The proposed method is simple, accurate and allows for high-speed sampling and considerably shorter analysis times. In addition, it requires inexpensive equipment and reagents and has easy operational conditions and no side effects, thus avoiding environmental pollution through toxic waste.